Household energy literacy: a critical review and a conceptual typology - Van den Broek, Karlijn (Energy research & social science, 2019)
The concept of energy literacy is increasingly receiving more research attention within the fields of education, economics and psychology. A wide variety of definitions and approaches characterise the energy literacy literature, making comparisons and generalizability of the findings problematic. This paper aims to review and organise the energy literacy literate that focus on the understanding of domestic electricity and gas use, by providing a framework for categorisation of the different conceptual and methodological approaches. Four types of household energy literacy are distinguished based on the existing literature: 1) device energy literacy, 2) action energy literacy, 3) financial energy literacy and 4) multifaceted energy literacy. The literature on each type of energy literacy is critically reviewed, focusing on the level of household energy literacy, its predictors and its relation to energy use. We call for more common principles and measures within the energy literacy research to allow for direct comparisons and longitudinal research on household energy literacy. This would greatly improve the quality and impact of the research, which in turn will help policy makers to decide how to address (which type of) energy literacy to facilitate domestic energy conservation.
Gesehen am 18.10.2019